AN OVERVIEW OF THE HERBAL MEDICINE USAGE TO MAINTAIN BODY IMMUNE SYSTEM AT THE UNIVERSITY OF AUGUST 17, 1945 JAKARTA - Purwati Purwati; Nur Yusdiyanti; Wimpy Agni Gautami; Dhea Anggraeni (AL ULUM: JURNAL SAINS DAN TEKNOLOGI, 2023)
The purpose of this study was to find out an overview of the herbal medicine usage as an immune booster at the University of August 17, 1945 Jakarta. The characteristics of the description of the use of herbal medicine to increase endurance obtained are the average in the age category (26-45 years) of 41.00%, the majority sex of men as much as 53.70%, the most education level is Bachelor (S1) of 42.10%. A type of medicinal plant to increase the body's resistance is red ginger (60.00%). Utilization of medicinal plants as a self-medication effort (78.90 %). An overview of recommending or giving the herbs to others for free (50.50%). The level of knowledge about traditional medicine within the University of August 17, 1945 Jakarta is good as many as 68 people (71.60%).